Sistem Pencatat Kwh Meter Terintegrasi Komputer Untuk Meningkatkan Layanan Pada Pelanggan - Abdul Haris (KILAT, 2017)
The accuracy of the reading and recording kWh meter greatly affect power usage so the need to develop a system that can provide accurate data such as the automation of the reading and recording the numbers kWh meter using mobile based application that can transmit data from readings stand meter to Server database wirelessly, with internet communication media. With the human resources that are reliable, the use of appropriate technology, and supported with a good application to be developed, it is expected the data reading and recording the numbers stand kWh meter can be recorded properly, quickly, and accurately so that the services of the company to customers will increase good and improve customer satisfaction levels